Variation of protease activity in coconut kernel in relation to variety, nut maturity and season - Panicker, L.M.; Usha, R.; Mandan, C.N. (International Coconut Community Journal, 2005)
Studies on the presence and involvement of proteases in the development and maturation of endosperm of Cocos nucifera L. revealed changes in concentration of proteases with the age of the nut, variety and season. More BAPNA (Na - Benzoyl DL - arginine p-nitroanilide) hydrolysing activity. Was observed at the immature stage and more gelatinolytic activity at the mature stage of the coconut endosperm development. There was apparent difference between seasons, the highest protease activity was during winter months.